Internal displacement in Asia and the Pacific: a human rights-based approach to law, policy and practice - Scott, M (Refugee Studies Centre, University of Oxford, 2022)
Adopting a human rights-based approach to examining law, policy and practice relating to displacement in the context of disasters and climate change highlights gaps between international and national standards, and realities on the ground.